The awful truth [videorecording (DVD)] - Dunne, Irene, 1898-1990; Grant, Cary, 1904-1986; Bellamy, Ralph, 1904-1991; D'Arcy, Alex, 1908-1996; Cunningham, Cecil, 1888-1959; Forbes, Mary, 1883-1974; Lamont, Molly, 1910-2001; Delmar, Viña, 1903-1990; Richman, Arthur, 1886-1944 (Columbia TriStar Home Entertainment, 2003)
A separated couple sabotages each other's love affairs while waiting for their divorce decree to become final.